If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7p + 51 = 96 Reorder the terms: 51 + 7p = 96 Solving 51 + 7p = 96 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-51' to each side of the equation. 51 + -51 + 7p = 96 + -51 Combine like terms: 51 + -51 = 0 0 + 7p = 96 + -51 7p = 96 + -51 Combine like terms: 96 + -51 = 45 7p = 45 Divide each side by '7'. p = 6.428571429 Simplifying p = 6.428571429
| 4(2x-3)-8=9-(5x-6) | | 3(x-7)=x+15 | | 3C+8=20 | | 8y/15-2=8-5y/3 | | y=18-x^2+3x | | 8x-71=3x-11 | | 4x^2+4xy^2+y^4=0 | | -5x^4+80x^2=0 | | 54z-(40z+36)= | | 19a+11b+4c+5c-3b-6a= | | 4x^2+4xy^2+4y^4=0 | | 2x^3-5x^2-4x-12=0 | | 8n^2+16-42=0 | | 15=-4+7 | | (x-7)(x+9)= | | (45)/(5/6) | | 12-2k=16+2k | | 3n^2-48=0 | | 45/5/6 | | 42x-18=84 | | -20x+4y=32 | | (n+4)*10=90 | | 2n^2-4n+10=0 | | 21=6/100x | | (X+9)(x-3)(x+4)=(x+7)(x+4)(x-2) | | (n-4)*4=16 | | 3/4y-3/2y | | -3n^2-n+13=0 | | 1/4(h+8)=9 | | 5(k-3)-8=6k-(5k-1) | | 3/4-3/2 | | ((2x^3y^2)/(-x^2y^5))^-2 |